Combination chemotherapy plus dasatinib leads to comparable overall survival and relapse‐free survival rates as allogeneic hematopoietic stem cell transplantation in Philadelphia positive acute lymphoblastic leukemia. (23rd April 2019) - Chang, Jeremy; Douer, Dan; Aldoss, Ibrahim; Vahdani, Golnaz; Jeong, Ah‐Reum; Ghaznavi, Zunera; Zhang, Sherry; Yaghmour, George; Lee, Kum‐Ja; Weissman, Ashley; Akhtari, Mojtaba
Abstract: Background: The Philadelphia chromosome is associated with a poor prognosis in acute lymphoblastic leukemia (ALL). While hematopoietic stem cell transplantation (HSCT) has been regarded as a favorable treatment option in adult Philadelphia‐positive (Ph+) ALL, its benefit is less clear in the era of newer generation tyrosine kinase inhibitors (TKIs) like dasatinib. Methods: This was a retrospective study that analyzed the outcomes of adult patients with Ph+ ALL treated with either combination chemotherapy plus dasatinib or combination chemotherapy plus dasatinib followed by allogeneic HSCT. Results: A total of 70 patients were included; 30 (42.9%) underwent allogeneic HSCT while 40 (57.1%) received only chemotherapy plus dasatinib. In comparing overall survival (OS) rates, results between the 2 groups were similar with a 1‐year OS of 93.3% versus 100% ( P  = 0.20), 2‐year OS of 89.8% versus 86.2% ( P  = 0.72), and 3‐year OS of 76% versus 71.3% ( P  = 0.56) in the transplant versus nontransplant groups, respectively. The 3‐year relapse‐free survival (RFS) rates were also similar at 70.5% in the transplant group and 80.1% in the nontransplant group ( P  = 0.94). Subgroup analyses were performed for patients with specific poor prognostic factors (higher white blood count, older age, positive minimal residual disease status), but results again showed no significant survival difference between transplant and nontransplant patients. Conclusions: While HSCT has historically led to a survival advantage in Ph+ ALL, the results of our study demonstrate that it may have a less beneficial role in the era of newer generation TKIs such as dasatinib. Abstract : This retrospective cohort study demonstrates that chemotherapy plus dasatinib leads to comparable overall survival and relapse‐free survival rates as allogeneic hematopoietic stem cell transplantation for adult Philadelphia‐positive acute lymphoblastic leukemia. Given the potential morbidity and mortality associated with transplantation, it may serve a less beneficial role in this population in the era of newer generation tyrosine kinase inhibitors.